Modeling the Triboelectric Behaviors of Elastomeric Nonwoven Fabrics. Issue 2 (8th November 2021) - Wang, Yanan; Shim, Eunkyoung; He, Nanfei; Pourdeyhimi, Behnam; Gao, Wei
Abstract: Theoretical modeling of triboelectric nanogenerators (TENGs) is fundamental to their performance optimization, since it can provide useful guidance on the material selection, structure design, and parameter control of relevant systems. Built on the theoretical model of film‐based TENGs, here, an analytical model is introduced for conductor‐to‐dielectric contact‐mode nonwoven‐based TENGs, which copes with the unique hierarchical structure of nonwovens and details the correlation between the triboelectric output (maximum transferred charge density) and nonwoven structural parameters (thickness, solidity, and average fiber diameter). A series of styrene–ethylene–butylene–styrene nonwoven samples are fabricated through a melt‐blowing process to map nonwoven structural features within certain ranges, while an ion‐injection protocol is adopted to quantify the triboelectric output with superior consistency and reproducibility. With a database containing structural features and triboelectric output of 43 nonwoven samples, a good model fitting is achieved via nonlinear regression analysis in Python, which also shows good predictive power and suggests the existing of tribo‐output maxima at a specific thickness, solidity, or average fiber diameter when other structural parameters are fixed. The model is also successfully applied to a group of polypropylene meltblown nonwovens, which verifies its universality on meltblown‐nonwoven‐based TENGs. Abstract : An analytical model is developed for nonwoven‐based triboelectric nanogenerators (TENGs) working at conductor‐to‐dielectric contact mode. The model fits well with different sets of experimental data at reasonable mean absolute percentage error (MAPE), and suggests that nonwoven triboelectric output reaches a maximum at a specific thickness, solidity, or average fiber diameter when other structural parameters are fixed.